2022
DOI: 10.48550/arxiv.2203.06203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the Inner Circumgalactic Medium and Quasar Illumination around the Reddest `Extremely Red Quasar' (ERQ)

Marie Wingyee Lau,
Fred Hamann,
Jarred Gillette
et al.

Abstract: Dusty quasars might be in a young stage of galaxy evolution with prominent quasar feedback. We study a population of luminous, extremely red quasars at redshifts 𝑧 ∼ 2-4 that has a suite of extreme spectral properties that may all be related to exceptionally powerful quasar-driven outflows. We present Keck/KCWI observations of the reddest known ERQ, at 𝑧 = 2.3184, with an extremely fast [O ] 𝜆5007 outflow at ∼6000 km s −1 . The Ly𝛼 halo spans ∼100 kpc. The halo is kinematically quiet, with velocity dispers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 93 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Besides J1150+5048, we found that other high EW AGN in our catalog are all narrow-line AGN with FWHM ∼ 1000 km s −1 , corresponding to the velocity dispersion of ∼ 400 km s −1 . Lau et al (2022) also found that the Lyα halo of the ERQ they studied is kinematically quiet with the velocity dispersion of ∼ 300 km s −1 .…”
Section: Extremely Red Quasar With Strong Windsmentioning
confidence: 76%
See 2 more Smart Citations
“…Besides J1150+5048, we found that other high EW AGN in our catalog are all narrow-line AGN with FWHM ∼ 1000 km s −1 , corresponding to the velocity dispersion of ∼ 400 km s −1 . Lau et al (2022) also found that the Lyα halo of the ERQ they studied is kinematically quiet with the velocity dispersion of ∼ 300 km s −1 .…”
Section: Extremely Red Quasar With Strong Windsmentioning
confidence: 76%
“…Unfortunately, the C III] λ1909 emission is out of the HETDEX wavelength range. Lau et al (2022) suggested that the the ionization parameter can be assumed to be lg U ∼ −1. The C IV λ1549/He II λ1640 ratio of ∼ 1 in at the Lyα density peak (shown by the cyan circle) would suggest a metallicity of ∼ Z .…”
Section: J1150+5048mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the past decade, integral field units with spectroscopic capability have discovered an abundance of extragalactic gaseous structures, including gaseous bridges between galaxies and quasars, 5,6 enormous hundreds-of-kpc-sized gas clouds, 7,8 and extensive gaseous haloes detected in a variety of emission lines including Lyα, [Oii], and Mg ii. [9][10][11][12] These techniques work well for medium to high redshift observations, where bright UV lines such as the Lyα λ1216 and Mg ii λ2796, 2803 emission lines are redshifted into the visible wavelength regime and where the 1 arcmin 2 fields of view of these instruments can cover an appreciable area around the targeted galaxies. In the local universe, though, the bright UV emission lines are not accessible from the ground and while visible wavelength emission lines such as Hα and [Oiii] are accessible, they are an order of magnitude fainter, requiring sensitivity to surface brightnesses down to ∼ 10 −20 erg cm −2 s −1 arcsec −2 to detect.…”
Section: Introductionmentioning
confidence: 99%